The Production of Striped Catfish (Pangasius hypophthalmus) In Intensive Cultivation Reviewed From Soil Chemistry Parameters of Red Yellow Podzolic In Different Age - Fadhli, Muhammad; Hasibuan, Saberina; Pamukas, Niken Ayu (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This study aims to determine the striped catfish production reviewed from the intensive cultivation of the soil chemical parameters of red-yellow podzolic an age of 0-5 years, 6-10 years, 11-15 years and 16-20 respectively. The method used in this study is the experimental method using a completely randomized design (CRD) with 1 factor, 4 levels of treatment and 3 replications, with the treatment are: P1 (intensive pond of catfish aquaculture aged 0-5 years), P2 (intensive pond of catfish aquaculture aged 6-10 years), P3 (intensive pond of catfish aquaculture aged 11-15 years) and P4 (intensive pond of catfish aquaculture aged 16-20 years). The results showed that the striped catfish production in P4 (pond aged 16-20 years) is the best treatment which has a high production of 6.4 kg/m2, with the survival rate of 66,7% and low feed conversion ratio of 1.9%, that supported by the good variety of parameters chemical soil classified, namely: total-N soil of 0,21%, P2O5 capacity of 177.9 ppm, the value of organic material content of 2.20%, cation exchange capacity (CEC) of 10.17% and C/N ratio of 6.14. Water quality parameters during recorded research period are 5.8 to 7.4 pH and temperature ranges 25,5-29,5oC, DO ranged from 1.9 to 5.8 mg/L. The range of pH, temperature and DO is quite good for striped catfish farming.Keywords: Production of striped catfish (Pangasius hypophthalmus), Soil Chemistry